Purchasing Decisions: The Analysis Effect Of The Variables Life Style, Celebrity Endorser, And Brand Image - Meilaty Finthariasari Finthariasari; Ratnawili Ratnawili; Nurman Halim (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2022)
This study aims to analyze the influence of Life Style, Celebrity Endorser and Brand Image on Purchase Decisions for Adidas Brand Sports Products in Gading Cempaka District, Bengkulu City, both partially and simultaneously. The object of this research is consumers or users of Adidas brand sports products in Gading Cempaka District, Bengkulu City, with incidental sampling method. The number of respondents in this study were 130 people. The data collection method was using a questionnaire and then the data was processed using SPSS version 24.. This research used the multiple linear regression data analysis technique, the results of this research can be concluded that the life style variable has a positive and significant effect on purchasing decisions, celebrity endorsers have a positive and significant effect on purchasing decisions, brand image has a positive and significant effect on purchasing decisions